Scientific collaboration in Peruvian biomedical journals - Huamaní, Charles (2011)
Background: Products of research activities in medicine are mainly expressed in scientific journals; these products are subject to quantification and may be registered in specialized databases. Objectives: To determine socialization and interaction of Peruvian researchers and research institutions in order to identify possible critical knots where media intervention might help improving and increasing scientific production in medicine. Design: Bibliometrical study. Institution: Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Bibliographic material: Scientific papers published during 2005-2008 in SciELO Peru database. Interventions: Only scientific papers were selected, identifying authorship and institutional affiliation. Authorship and institutional collaboration were analyzed. Main outcome measures: Authors’ signatures index, frequencies, percentages and collaboration nets. Results: Four hundred and ninety three papers were analyzed comprising 2 131 signatures of 1 540 authors and 271 institutions; 56,2% were elaborated jointly by two institutions; 70,5% of researchers had only one paper registered. Most productive institutions were Universidad Nacional Mayor de San Marcos and Universidad Peruana Cayetano Heredia, with 138 and 125 articles respectively. Conclusions: National medical research is accomplished by few persevering researchers and few research nuclei mainly from universities that appear centralized and with moderate aperture to other developing knots.